Early Effects of Cognitive-Impairment Friendly Community on Health Care Utilization in China: Evidence from Administrative Data - Jingyi Ai; Xi Chen; Jin Feng; Yufei Xie (Institute of Labor Economics (IZA), 2025)
The study examines the early effects of cognitive-impairment (CI) friendly communities on health care utilization among older adults in Shanghai, China. By exploiting the rollout of CI-friendly communities and employing a difference-in-differences approach, we evaluate the impact of CI-friendly communities. We find that CI-friendly communities significantly increase the probability and frequency of visiting cognition-disease-related departments (CRD) by 0.7 (13.73%) percentage points and 0.02 (17.24%) times, respectively. In particular, the effect is more pronounced for individuals not previously received CRD care. The dominant mechanisms may include information and early screening effects. Additionally, CI-friendly communities affect health care utilization in other positive ways, such as reducing emergency room (ER) visits and promoting primary care use.
Keywords: I18; J14; I11; 330; CI-friendly community; health care utilization; awareness of cognitive impairment